Crystal structure of dutasteride (Avodart), C27H20F6N2O2. Issue 3 (13th August 2014) - Kaduk, James A.; Crowder, Cyrus E.; Zhong, Kai; Fawcett, Timothy G.; Suchomel, Matthew R.
Abstract : Commercial dutasteride crystallizes in the orthorhombic space group P 21 21 21 (#19), with a  = 7.587 44(3), b  = 9.960 80(5), c  = 33.500 42(12) Å, V  = 2531.862(17) Å 3, and Z  = 4. The structure was solved and refined using synchrotron powder diffraction data, Rietveld, and density functional techniques. The most prominent feature of the structure is a zigzag chain of strong N–H···O = C hydrogen bonds along the a -axis. The powder pattern has been submitted to ICDD for inclusion in future releases of the Powder Diffraction File™.